Abordagem ativa da acústica no ensino médio com a confecção de artefatos musicais pelos alunos - Pereira, Rodrigo Machado (2013)
This paper aims to present, as experience report, an active approach to teaching about the content of Acoustics by contextualized knowledge of music, from the design and construction of sound artifacts with low cost materials for high school students. The activities were conducted in a public school of the state of São Paulo in the city of Mogi Guaçu. The acoustic content were worked both quantitatively and qualitatively. Qualitative analysis was applied to the study of the properties of sound musical artifacts produced by students taking into account the aspects of production, propagation and amplification of sound. The quantitative phase of didactic activity was conducted using the software "Soundcard Scope V1.4" which allowed the harmonic analysis of the sound produced by these devices and captured by the sound card of a computer. The active approach we present has its theoretical foundations in education and social constructivist approach is inspired by Kuhn's epistemology. Process is guided by social contextualization of knowledge and consideration, the teacher, the students' spontaneous conceptions, as well as the cooperative work between them. The mediation of the teacher tried to always be located within the Zone of Proximal Development (ZPD) of the students and thus contributing to the formalization of scientific concepts worked. We have also added strategies such as the use of Information and Communication Technologies (ICT) and the approach of the relations between Science, Culture and Society. The material production of students through the sound artifacts that confected, and the monitoring of the production process of these signs indicate that the work has motivated students for learning physics, and also contributed to make it meaningful to them, some concepts of acoustics.